The Role of PIEZO1 in Urinary Bladder Function and Dysfunction in a Rodent Model of Cyclophosphamide-Induced Cystitis - Beča, Katharine I. K.; Girard, Beatrice M.; Heppner, Thomas J.; Hennig, Grant W.; Herrera, Gerald M.; Nelson, Mark T.; Vizzard, Margaret A. (Frontiers in Pain Research, 2021)
In the urinary bladder, mechanosensitive ion channels (MSCs) underlie the transduction of bladder stretch into sensory signals that are relayed to the PNS and CNS. PIEZO1 is a recently identified MSC that is Ca2+ permeable and is widely expressed throughout the lower urinary tract. Recent research indicates that PIEZO1 is activated by mechanical stretch or by pharmacological agonism via Yoda1. Aberrant activation of PIEZO1 has been suggested to play a role in clinical bladder pathologies like partial bladder outlet obstruction and interstitial cystitis/bladder pain syndrome (IC/BPS). In the present study, we show that intravesical instillation of Yoda1 in female Wistar rats leads to increased voiding frequency for up to 16 hours after administration compared to vehicle treatment. In a cyclophosphamide (CYP) model of cystitis, we found that the gene expression of several candidate MSCs (Trpv1, Trpv4, Piezo1, and Piezo2) were all upregulated in the urothelium and detrusor following chronic CYP-induced cystitis, but not acute CYP-induced cystitis. Functionally with this model, we show that Ca2+ activity is increased in urothelial cells following PIEZO1 activation via Yoda1 in acute and intermediate CYP treatment, but not in naïve (no CYP) nor chronic CYP treatment. Lastly, we show that activation of PIEZO1 may contribute to pathological bladder dysfunction through the downregulation of several tight junction genes in the urothelium including claudin-1, claudin-8, and zona occludens-1. Together, these data suggest that PIEZO1 activation plays a role in dysfunctional voiding behavior and may be a future, clinical target for the treatment of pathologies like IC/BPS.